Diseño de un sistema de generación de electricidad a partir de la energía eólica en un parque del barrio las Flores de la ciudad de Barranquilla (2021)
In this project, the design of an electricity generation system from wind energy was evidenced for the 86 Park of the Las Flores neighborhood of the city of Barranquilla, in order to improve the safety of its residents due to deficiency in lighting, due to the poor provision of electrical service by the energy provider at night and collaborating with the reduction of environmental pollution in the world due to the use of non-renewable energies. The design includes the improvement of the lighting, the repair of the park's connectivity system, the sizing of the required electrical loads. The characterization of wind energy in the place where the design projects. mathematical development was evidenced, the sizing and selection of all the elements that make up the system, the geometric modeling of the wind turbine in SolidWorks software, the simulation of the operation of the wind turbine and general planimetry of the project developed in the AutoCAD design software. Having as a final result the list of required components and the budget, which, since it is a considerable amount, proposes to look for lower-cost alternatives for future projects, how could it be the design and manufacture of an autogenerator with low-cost of materials.